2000
DOI: 10.1111/j.1574-695x.2000.tb01405.x
|View full text |Cite
|
Sign up to set email alerts
|

Production, characterization, and application of monoclonal antibodies which distinguish four glucosyltransferases fromStreptococcus sobrinus

Abstract: A 1,3-alpha-glucan synthase (GTF-I), a highly branched 1, 6-alpha-glucan synthase (GTF-U) and a 1,6-alpha-glucan synthase (GTF-T) were purified to near homogeneity from the culture fluid of Streptococcus sobrinus strain B13N (serotype d) and characterized. In addition, a crude preparation of a recombinant oligo-isomaltosaccharide synthase (rGTF-S) was prepared from a cell-free extract of Escherichia coli MD124 transformant. Using four homogeneous GTF preparations including previously purified rGTF-S as antigen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…It has been found that simultaneous synthesis of glucans by GtfB and GtfC is essential for formation of high-density biofilm with high adhesion, which promotes their binding to an apatite surface [7]. S. sobrinus strains extracellularly produce at least four kinds of Gtfs: (1→3)-α-d-glucan synthase (GtfI) and (1→6)-α-d-glucan synthase (GtfU), (1→6)-α-d-glucan synthase (GtfT), and an oligo-isomaltosaccharide synthase (GtfS) [8]. Glucosyltransferases and their polysaccharide products have been shown to be fundamental virulence factors in the pathogenesis of dental caries because they are responsible for close adhesion to the tooth surface in the presence of sucrose.…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that simultaneous synthesis of glucans by GtfB and GtfC is essential for formation of high-density biofilm with high adhesion, which promotes their binding to an apatite surface [7]. S. sobrinus strains extracellularly produce at least four kinds of Gtfs: (1→3)-α-d-glucan synthase (GtfI) and (1→6)-α-d-glucan synthase (GtfU), (1→6)-α-d-glucan synthase (GtfT), and an oligo-isomaltosaccharide synthase (GtfS) [8]. Glucosyltransferases and their polysaccharide products have been shown to be fundamental virulence factors in the pathogenesis of dental caries because they are responsible for close adhesion to the tooth surface in the presence of sucrose.…”
Section: Introductionmentioning
confidence: 99%
“…MAbs are important biomaterials in the detection and identification of pathogens and have been widely applied for the development of specific and sensitive detection methods. 16 19 A monoclonal antibody against ALV-J has been successfully prepared and used to establish an indirect immunofluorescence assay (IFA) and an ultrasensitive electrochemical immunoassay. 20 22 In our laboratory, an ALV-A monoclonal antibody was also successfully developed and utilized in a rapid and specific colloidal gold test strip.…”
Section: Introductionmentioning
confidence: 99%
“…MAbs are important biomaterials in the detection and identification of pathogens and have been widely applied for the development of specific and sensitive detection methods. A monoclonal antibody against ALV-J has been successfully prepared and used to establish an indirect immunofluorescence assay (IFA) and an ultrasensitive electrochemical immunoassay. In our laboratory, an ALV-A monoclonal antibody was also successfully developed and utilized in a rapid and specific colloidal gold test strip. , Recently, a MAb against ALV-K that can recognize an epitope of the gp85 protein containing 17 amino acid residues ( 129– AFGPRSIDTLSDWSRPQ –145 ) has been reported; however, it is difficult to apply it clinically due to the lack of reports about its biological characteristics such as specificity, stability, and antigenic epitope structure. In this study, a new MAb against another ALV-K gp85 epitope ( 217– RRNYT –221 ) was successfully prepared, and its biological characteristics were clarified, which contributes to the establishment of novel and specific detection methods for ALV-K.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, four different Gtf genes, namely GtfJ, GtfK, GtfL , and GtfM , were identified in S. salivarius ATCC 25975 (Giffard et al, 1991, 1993; Simpson et al, 1995b). Examining these Gtf enzymes revealed that, similar to S. mutans GtfB and GtfC, S. downei GtfI, S. sobrinus GtfI, and S. salivarius GtfJ and GtfL all synthesize WIG, while other Gtfs, similar to S. mutans GtfD, mainly synthesize WSG (Russell et al, 1987, 1990; Abo et al, 1991; Hanada et al, 1991; Simpson et al, 1995a; Nanbu et al, 2000).…”
Section: Introductionmentioning
confidence: 99%